INTEGRATING GENERATIVE AI IN ARTS DESIGN EDUCATION: ENHANCING PBL FOR CRITICAL THINKING (Proceedings of the International Conference on Education, 2025)
Generative AI such as ChatGPT, Midjourney and Stable Diffusion are disrupting arts design education, providing tools to promote critical thought, creativity and collaboration. Despite the emergence of these tools, their use is still far from integrated into project-based learning (PBL) frameworks and very little guidance has been provided to educators on how they can use AI effectively to further pedagogical aims. This literature review thus fills this research gap by systematically reviewing the existing research on the application of generative AI in design education, specifically its potential to facilitate critical thinking, innovative problem-solving, and collaborative learning processes. By synthesizing relevant knowledge from various disciplines, the review highlights specific approaches that can make the integration of generative AI into crucial phases of the PBL cycle (including idea generation, design refinement and team dynamics) more feasible and actionable. Additionally, it addresses key challenges, such as ethical implications, intellectual property issues, and the dangers of over-reliance on AI, while providing guidance on overcoming these obstacles. Results suggest generative AI can add to students’ abilities with it, blurring the lines between long established art design pedagogies and current digital practice rather than replacing them. Strengths and limitations This study's limitations were the use of secondary data and the emerging literature. Nevertheless, the review offers a useful structure for the integration of generative AI in the PBL context and announces the areas to be researched further, for example, longitudinal research on effects on learning and interdisciplinary research. Implications emphasize the importance of balanced uptake: making the most of AI’s positive contributions to creativity and critique, while protecting students’ agency and capacity for original thought.
Keywords: Generative AI; Arts Design Education; Project-Based Learning; Critical Thinking; Creativity; AI Tools